Interpersonal and Organizational Conflict Management in Schools: Enhancing the Effectiveness of Educational Human Resources in the Context of Educational Transformation - Qodir, Abdul; Siminto; Hanif, Muh. (PT. LITERASI SAINS NUSANTARA, 2025)
The ongoing transformation of education, which demands collaboration, innovation, and rapid adaptation, presents significant challenges to the effectiveness of educational human resources, particularly when interpersonal and organizational conflicts emerge as structural and psychological barriers within school environments. This study is a literature review using a descriptive qualitative approach that aims to analyze the dynamics of conflict management in schools and its contribution to strengthening human resources in the context of educational transformation. Data were collected from 40 scholarly articles published between 1967 and 2025 via Google Scholar and other credible academic sources, then strictly selected down to 22 relevant articles. The review findings indicate that conflict management based on collaborative approaches, transformative leadership, and organizational culture reinforcement plays a crucial role in improving the performance effectiveness of educators and school staff. Analyzed case studies show that schools successfully managing conflicts constructively are able to create a more productive, adaptive work environment that supports the success of school-based community engagement programs. These findings affirm that conflict management must become an integral part of educational human resource development strategies to fully support the national education reform agenda.